The Utilization of Basic Oxygen Furnace Slag as Fine Aggregates in Concrete: Physical, Mechanical, and Durability Properties - Hakan Ozkan (Journal of Sustainable Construction Materials and Technologies, 2025)
This study examines the feasibility of using basic oxygen furnace slag (BOFS) as an alternative to fine crushed limestone aggregate in concrete. BOFS is sourced from two steel production facilities in Türkiye, designated as I-BOFS and E-BOFS. The experimental results showed that as the E-BOFS aggregate replacement ratio increased, the water-to-cement (w/c) ratio increased to maintain the target workability. The concrete mixtures incorporating E-BOFS exhibited consistent reductions in the compressive strength with an increase in the BOFS ratio. At the same time, I-BOFS maintained higher compressive strength, with only minor losses up to 80% of the substitution ratio. Flexural strength was similarly affected, with notable reductions at higher BOFS levels, though I-BOFS performed better. Water penetration depth values remained similar to the reference concrete for both BOFS sources up to a 60% replacement ratio. Conversely, higher replacement levels led to increased water permeability. In summary, the study concludes that the inherent BOFS aggregate characteristics, such as mechanical strength, water absorption, and fines content, significantly affect the fresh and hardened concrete properties, which might limit their utilization ratio in concrete and require detailed testing before using such aggregates.